METODE KETELADANAN PERSPEKTIF PENDIDIKAN ISLAM - Ali Mustofa (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2019)
Based on phenomena At present, children experience an exemplary crisis. This happened because, at least the mass media raised the theme of exemplary figures for children. Television shows, for example, are dominated by entertainment programs in various variations, soap operas, or celebrity gossip shows that cannot be expected to provide examples of Islamic life as a whole. In this exemplary crisis, educators are an important base. Therefore, educators must have high awareness, to be role models in the process of forming Islamic moral character of children. The results of this study prove that: exemplary in education is an effective method / way of preparing children in terms of morals, mental and social. Psychologically exemplary as a method of Islamic education because it sees basically human beings from a young age already have a sense of wanting to imitate the movements or behavior of parents, teachers, and the environment. In this regard parents are required, the teacher has qualities that are exemplary as practiced by the Prophet. like the nature of patience, affection, morality, tawadhu ', zuhud and just.